188k views
3 votes
I’m struggling, if someone can explain this please

I’m struggling, if someone can explain this please-example-1
User Allisen
by
6.8k points

2 Answers

3 votes

Answer:

5

Explanation:

We already know the square root of 9 is 3 because 3 times 3 equals 9

So now the equation is 6 * 3/3 - 1

3 divided by 3 is 1

6 * 1-1

6 times 1 is 6

6-1

You should get 5

User Steve Baek
by
7.0k points
2 votes

Answer:

5

Explanation:

6*3÷√9-1

=6*3÷3-1

=6*(3/3)-1

=6*1-1

=6-1

=5

User Max Xu
by
6.1k points